A new characterization of \(L_2\)(q) where q = \(p^n\) < 125 - He, Li-Guan; Chen, Gui-Yun (Italian Journal of Pure and Applied Mathematics, 2011)
It is a well-known topic to characterize a ¯nite simple group by using two quantities, the order of G and πe(G) in the past 30 years, where πe(G) denotes the set of orders of elements in G. Recently this topic has been finished by V.D. Mazurov, et al. Here the authors will try to characterize some finite simple groups by using less quantities and have successfully characterized L2(q), where q = pn < 125, by using the order of L2(q) and the three largest element orders of L2(q).